2009
DOI: 10.1080/00288330909509977
|View full text |Cite
|
Sign up to set email alerts
|

Sound production in Caribbean spiny lobsterPanulirus argusand its role in escape during predatory attack byOctopus briareus

Abstract: The production of sound (commonly called stridulation) in spiny lobsters when disturbed by humans is well documented but its function during encounters with natural predators remains largely undocumented. Caribbean spiny lobsters Panulirus argus stridulate during tailflip escape attempts in response to grasping of the carapace or antennae by human divers. We hypothesised that stridulating may be effective against predators like octopus which grasp the carapace and antennae during attacks in a way similar to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 50 publications
2
47
0
1
Order By: Relevance
“…This result is in agreement with the findings of other authors (Lindberg 1955, Moulton 1957, Hazlett & Winn 1962, MeyerRochow & Penrose 1974, 1976, Patek 2001, Patek & Oakley 2003, Bouwma & Herrnkind 2009). These authors assumed that the lobsters only produced sounds in an anti-predator context.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This result is in agreement with the findings of other authors (Lindberg 1955, Moulton 1957, Hazlett & Winn 1962, MeyerRochow & Penrose 1974, 1976, Patek 2001, Patek & Oakley 2003, Bouwma & Herrnkind 2009). These authors assumed that the lobsters only produced sounds in an anti-predator context.…”
Section: Discussionsupporting
confidence: 83%
“…These authors assumed that the lobsters only produced sounds in an anti-predator context. Moreover, Bouwma & Herrnkind (2009) demonstrated that spi ny lobsters Panulirus argus with an experimentally disabled stridulating apparatus were attacked and killed by predators more frequently than intact spiny lobsters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations